Human Engineered Heart Muscles Engraft and Survive Long Term in a Rodent Myocardial Infarction Model. Issue 8 (25th September 2015) - Riegler, Johannes; Tiburcy, Malte; Ebert, Antje; Tzatzalos, Evangeline; Raaz, Uwe; Abilez, Oscar J.; Shen, Qi; Kooreman, Nigel G.; Neofytou, Evgenios; Chen, Vincent C.; Wang, Mouer; Meyer, Tim; et al.
<x xml:space="preserve">Abstract</x> Rationale: Tissue engineering approaches may improve survival and functional benefits from human embryonic stem cell–derived cardiomyocyte transplantation, thereby potentially preventing dilative remodeling and progression to heart failure. Objective: Assessment of transport stability, long-term survival, structural organization, functional benefits, and teratoma risk of engineered heart muscle (EHM) in a chronic myocardial infarction model. Methods and Results: We constructed EHMs from human embryonic stem cell–derived cardiomyocytes and released them for transatlantic shipping following predefined quality control criteria. Two days of shipment did not lead to adverse effects on cell viability or contractile performance of EHMs (n=3, P=0.83, P=0.87). One month after ischemia/reperfusion injury, EHMs were implanted onto immunocompromised rat hearts to simulate chronic ischemia. Bioluminescence imaging showed stable engraftment with no significant cell loss between week 2 and 12 (n=6, P=0.67), preserving ⩽25% of the transplanted cells. Despite high engraftment rates and attenuated disease progression (change in ejection fraction for EHMs, −6.7±1.4% versus control, −10.9±1.5%; n>12; P=0.05), we observed no difference between EHMs containing viable and nonviable human cardiomyocytes in this chronic xenotransplantation model (n>12; P=0.41). Grafted cardiomyocytes showed enhanced sarcomere alignment and increased connexin 43 expression at 220 days after transplantation. No teratomas or tumors were found in any of the animals (n=14) used for long-term monitoring. Conclusions: EHM transplantation led to high engraftment rates, long-term survival, and progressive maturation of human cardiomyocytes. However, cell engraftment was not correlated with functional improvements in this chronic myocardial infarction model. Most importantly, the safety of this approach was demonstrated by the lack of tumor or teratoma formation.